Long-term explosive degassing and debris flow activity at West Mata submarine volcano - Dziak, R P; Bohnenstiehl, D R; Baker, E T; Matsumoto, H; Caplan-Auerbach, J; Embley, R W; Merle, S G; Walker, S L; Lau, T-K.; Chadwick Jr., W W (GEOPHYSICAL RESEARCH LETTERS, 2015)
West Mata is a 1200m deep submarine volcano where explosive boninite eruptions were observed in 2009. The acoustic signatures from the volcano's summit eruptive vents Hades and Prometheus were recorded with an in situ (similar to 25m range) hydrophone during ROV dives in May 2009 and with local (similar to 5km range) moored hydrophones between December 2009 and August 2011. The sensors recorded low frequency (1-40Hz), short duration explosions consistent with magma bubble bursts from Hades, and broadband, 1-5min duration signals associated with episodes of fragmentation degassing from Prometheus. Long-term eruptive degassing signals, recorded through May 2010, preceded a several month period of declining activity. Degassing episodes were not recorded acoustically after early 2011, although quieter effusive eruption activity may have continued. Synchronous optical measurements of turbidity made between December 2009 and April 2010 indicate that turbidity maxima resulted from occasional south flank slope failures triggered by the collapse of accumulated debris during eruption intervals.
Keywords: ROV Jason (Remotely Operated Vehicle)